THE EFFECT OF MINDFULNESS – BASED COGNITIVE TRAINING ON REDUCING ANXIETY IN ADOLESCENTS OF DIVORCED FAMILIES - Yousefi, Nahid; Avarsin, Faride Maleki; Toutounchi, Zahra (International Journal of Psychosocial Rehabilitation, 2020)
divorce is one of the most stressful life events for both parents and children. Parental divorce includes wide range of changes and it needs extensive reorganizing of family that during the time, effect the compatibility of adolescents.the aim of this study is examination effectiveness of mindfulness – based cognitive training on reducing anxiety in adolescents of divorced families. design of current study is semi – experimental one with pre and posttest stages and one group control, and population of this research was all of teen female students that were studying in Tehran in 2016. They were selected by randomized cluster sampling that from twenty – two regions of Tehran, region one was selected, and from all schools of this region (1 school), 30 persons were selected by purposive sampling method and then randomly, were devised in experimental and control groups (15 persons in experimental and 15 persons in control group). Experimental group had 8 ninety – minutes sessions regarding mindfulness – based cognitive training plans. But control group had no psychological services. This people were completed two questionnaires before and after interventions. The tools used in this study include Beck Anxiety Inventory. analyses of covariance show that there are significant differences in decreasing anxiety between experimental and control group (p < 0.01). results of this research show that mindfulness – based cognitive training for decreasing anxiety in teenagers of divorced families is effective.